Comparison between capillary electrophoresis and high performance liquid chromatography for detection and quantification of Hb constant spring [Hb CS; α142, Term→Gln (TAA>CAA in α2)] - Jarurin Waneesorn (2018)
Hb Constant Spring [Hb CS; α142, Term→Gln (TAA>CAA in α2)] is often missed by routine laboratory testing since its mRNA as well as gene product are unstable and presented at a low level in peripheral blood. This study aimed to analyze the efficacy of capillary electrophoresis (CE) and high performance liquid chromatography (HPLC) for detecting and quantifying Hb CS in 19 heterozygotes and 14 homozygotes with Hb CS as well as 10 Hb H-CS disease subjects who were detected by molecular analysis. In the CE electrophoregram, Hb CS was seen at zone 2 and was observed in all samples, while the chromatogram of Hb CS peaks was found in 26.32% heterozygotes, 42.86% homozygotes and 90% Hb H-CS disease subjects, respectively. In addition, the Hb CS levels in each group of subjects quantified by CE were significantly higher than those quantified by HPLC. Based on the CE method, the lowest Hb CS level was found in the heterozygotes, whereas the highest level was found in the Hb H-CS disease patients. Therefore, the CE method was superior to the HPLC method for detecting Hb CS. Furthermore, the level of Hb CS quantified by CE proved useful in screening heterozygotes and homozygotes with Hb CS as well as Hb H-CS disease. © 2011 Informa Healthcare USA, Inc.